Classification of Science According to As-Suyuthi (Study of Verses on Science in the Book Al-Itqon Fi ‘Ulum Al-Qur’an) - Muhammad Farhan Iskandar; Ziyadul Haq; Arrazy Hasyim (al-Afkar, Journal For Islamic Studies, 2026)
Science that is currently progressing throughout the world, initially came from the embryo of Muslim scholars' thoughts. In its journey, a paradigm of dichotomy of science and religion emerged which caused a separation between religion and science, as well as religious people and scientists. However, it cannot be denied that science that is currently developing rapidly, in its historical center is Muslim scholars who took part in studying Science based on the first source of Islamic law, namely the Qur'an, one of whom was the 'ulama who lived during the Mamluk Dynasty Imam as-Suyuthi. There are many verses of the Qur'an that indicate knowledge, but other evidence is needed to strengthen it. Departing from this paradigm, the author then analyzes the process of how Imam as-Suyuthi carried out the process of classifying the sciences that originate from the Qur'an which we call istinbath. First, the author determines the verses of the Qur'an, or the opinions of other scholars that indicate or discuss a science. Then, he includes evidence in the form of verses, narrations that are interrelated in the process of istinbath as-Suyuthi until finally a science can be determined, and the branches of science from it.